Takotsubo cardiomyopathy and pituitary apoplexy: a case report - Chun Yang; Xiu Han; Yuan Du; Ai-qun Ma (BMC Cardiovascular Disorders, 2020)
Abstract Background Takotsubo cardiomyopathy (TTC) has been widely recognized in recent decades and is triggered by either physical or psychological stressors. Case presentation A 70-year-old woman presented to the Emergency Department due to confusion, hypotension, fever, chills, and cough. She had a one-year history of diabetes insipidus. Pituitary function examination at admission revealed decreased thyroid, sex and adrenal hormones. Pituitary MRI displayed findings suggestive of nonhemorrhagic pituitary apoplexy. Electrocardiogram (ECG) revealed T-wave inversion and extended QT interval. Transthoracic echocardiogram (TTE) showed left ventricular apical dysplasia and ballooning, accompanied by reduced left ventricular ejection fraction. Coronary angiography (CAG) revealed no obvious coronary arterial stenosis. The left ventriculogram demonstrated an octopus clathrate appearance. Most ECG and TTE changes recovered 10 days later. Conclusions To the best of our knowledge, this is the first report of newly diagnosed TTC associated with pituitary apoplexy.